2020
DOI: 10.1007/s11195-020-09619-2
|View full text |Cite
|
Sign up to set email alerts
|

Making Connections and Building Confidence: A Study of Specialist Dating Agencies for People with Intellectual Disabilities

Abstract: Dating agencies are a small, but growing sector of social care provision for people with intellectual disabilities. The research reported here is the first to explore, with 10 specialist agencies in the UK, why they were set up, how they operate, the barriers and problems they encounter and their success or otherwise in facilitating relationships for people with intellectual disabilities. A strong case is made for the proliferation of such services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Such a stance results from sexual ableism (Gill, 2015). Sexual ableism produces ID as a characteristic that disqualifies one from sexual agency and it negates the rights of these individuals as sexual beings (McCarthy et al, 2020). When it comes to sexuality for people with ID, they are often constructed as asexual, sexually inactive, or conversely, sexually deviant (Kulick & Rydström, 2015; Shakespeare, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Such a stance results from sexual ableism (Gill, 2015). Sexual ableism produces ID as a characteristic that disqualifies one from sexual agency and it negates the rights of these individuals as sexual beings (McCarthy et al, 2020). When it comes to sexuality for people with ID, they are often constructed as asexual, sexually inactive, or conversely, sexually deviant (Kulick & Rydström, 2015; Shakespeare, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…When McCarthy et al . (2020) asked people with ID about their experiences of using mainstream dating agencies, they found evidence of people being ‘ridiculed’ and ‘ignored’.…”
Section: Discussionmentioning
confidence: 99%
“…This was a surprising finding because even though there has been a significant movement towards addressing prejudice and negative stereotyping faced by people with ID, it has been found that negative societal attitudes are still commonplace. When McCarthy et al (2020) asked people with ID about their experiences of using mainstream dating agencies, they found evidence of people being 'ridiculed' and 'ignored'.…”
Section: Agreement On High and Low Attractiveness Ratingsmentioning
confidence: 99%
“…The first issue raised was strong support for dating and friendship agencies especially for people with intellectual disabilities (see McCarthy et al, 2020 for more details.) Unlike their experiences with mainstream dating services, which were very aversive (see above), the specialist agencies were found to be very supportive:
The support we had was fantastic.They'd sit… a few tables away, so we had the support, but we didn't have someone sat in between us over a candlelit dinner.
…”
Section: Methodsmentioning
confidence: 99%
“…Other studies in the programme gathered data from 10 specialist dating agencies and 40 family carers and support staff. Findings from the other studies are reported elsewhere (Bates, 2020;McCarthy et al, 2020). The whole research programme ran from October 2017-April 2019.…”
Section: Me Thodmentioning
confidence: 99%